Electronic, optical and thermoelectric properties of two-dimensional pentagonal SiGeC4 nanosheet for photovoltaic applications: First-principles calculations. (October 2021) - Bouziani, I.; Haman, Z.; Kibbou, M.; Essaoudi, I.; Ainane, A.; Ahuja, R.
Abstract: In this theoretical study, based on the density functional theory, we investigate the electronic, optical and thermoelectric properties of SiGeC4 nanosheet, within the framework of mBJ-GGA approximation (modified Becke–Johnson generalized gradient approximation). The calculated results indicate that the two-dimensional SiGeC4 compound is energetically, dynamically, thermally and mechanically stable in the pentagonal structure and shows semiconductor character with indirect and moderate bandgap. Also, it is found that this two-dimensional system presents high absorption and low reflectivity as well as high photoconductivity in the visible range. Furthermore, it is shown that the studied compound exhibits good thermoelectric performance with high electrical conductivity and Seebeck coefficient. These results render the two-dimensional pentagonal SiGeC4 nanosheet as strong absorber layer candidate in the next generation of photovoltaic devices. Highlights: Pentagonal SiGeC4 system has a semiconductor character with moderate band gap. SiGeC4 compound shows high absorption and low reflectivity in the visible side. SiGeC4 nanomaterial presents high optical conductivity in the visible wavelength range. Two dimensional SiGeC4 possesses high electrical conductivity and Seebeck coefficient. Pentagonal SiGeC4 nanosheet is a strong absorber layer candidate for photovoltaic devices.